Potential geographic distribution niche modeling based on bioclimatic variables of three species of Temnomastax Rehn and Rehn, 1942 (Orthoptera: Eumastacidae). Issue 21 (11th June 2017) - Olivier, Renan da Silva; Aranda, Rodrigo
ABSTRACT: Predictive modeling of geographic distribution based on ecological niche has become an important tool in ecology. It uses previous information about distribution of species and environmental variations associated with this distribution, restricting to the models the closest prediction of the ecological niche. The eumastacid grasshoppers are distributed mainly in the Neotropical region, and Temnomastacinae is the subfamily with the largest geographic distribution. Little is known about the biology of Eumastacidae, the only data available reporting the association between some grasshopper species and plants of several families. In the Cerrado only Temnomastax is recorded, which has a wide distribution in the central region of Brazil. The aim of this work was to determine the potential geographic distribution of three species of Temnomastax occurring in the Cerrado biome. We used 446 records of occurrence obtained in specialised literature, inventories, museums and photographs, from the following species: Temnomastax hamus, Temnomastax ricardoi and Temnomastax tigris . The niche modeling was generated with the bioclimatic model DOMAIN through DIVA-GIS. The potential geographic distribution of T . hamus is the largest among all Temnomastax species. Temnomastax ricardoi has its potential distribution in the central-north of Mato Grosso do Sul, in regions surrounding the type locality, while T. tigris . exhibits a restricted potential distribution along the carbonate arc of the Corumbá Formation, which outcrops in the region of Serra da Bodoquena and Corumbá, entering the eastern portion of Bolivia.